2019
DOI: 10.1038/s41598-019-45108-z
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the cryptochrome 2 and mitoguardin 2 genes are associated with the variation of lipid-related traits in Duroc pigs

Abstract: The genetic factors determining the phenotypic variation of porcine fatness phenotypes are still largely unknown. We investigated whether the polymorphism of eight genes ( MIGA2 , CRY2 , NPAS2 , CIART , ARNTL2 , PER1 , PER2 and PCK1 ), which display differential expression in the skeletal muscle of fasted and fed sows, is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Hofer et al [ 59 ] found that the silence of PEX6 affects adipocyte differentiation and increases peroxisomal fatty acid oxidation–reduction. For the CRY2 gene, Mármol-Sánchez et al [ 60 ] reported that the polymorphism of CRY2 was significantly associated with stearic acid content in the longissimus dorsi muscle in Duroc pigs. The Acyl-CoA Thioesterase 8 ( ACOT8 ) gene is located in the region of 47.67–48.83 Mb on SSC17.…”
Section: Resultsmentioning
confidence: 99%
“…Hofer et al [ 59 ] found that the silence of PEX6 affects adipocyte differentiation and increases peroxisomal fatty acid oxidation–reduction. For the CRY2 gene, Mármol-Sánchez et al [ 60 ] reported that the polymorphism of CRY2 was significantly associated with stearic acid content in the longissimus dorsi muscle in Duroc pigs. The Acyl-CoA Thioesterase 8 ( ACOT8 ) gene is located in the region of 47.67–48.83 Mb on SSC17.…”
Section: Resultsmentioning
confidence: 99%
“…In this comparison, control piglets upregulated SESN2 and ANPEP , which participate in stress response and inhibit mTOR-mediated cell growth 35 , and have proteolytic activity 36 , respectively. In turn, they upregulated a key gene in circadian rhythm regulation of energy homeostasis and lipid metabolism 37 , PER2 , as well as ANKRD1 , involved in muscle tissue development 38 and ARG2 , which has been suggested to be an adequate biomarker for feed efficiency 39 . Their counterparts increased the abundance of TNNT1 , which codes for a contractile apparatus protein that has been related to muscle growth 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The circadian-associated transcriptional repressor CIART is involved in the eye regression of cave molly ( Poecilia mexicana ) 114 , whereas turbot ciart proved to be differentially expressed in freshwater- versus seawater-acclimated fish 115 . A missense polymorphism in pig ciart was reported to be associated with backfat thickness 116 . Both the Asn and Ser residues in the polymorphic position 271 of turbot CIART are found in other teleost.…”
Section: Discussionmentioning
confidence: 99%